Adding a Fibular Strut Allograft to Intramedullary Nail and Cancellous Autograft During Stage II of the Masquelet Technique for Segmental Femur Defects: A Technique Tip. (July 2020) - Ramos, Omar; Mariorenzi, Michael; Johnson, Joey P.; Hayda, Roman A.
Abstract : Reconstruction of segmental diaphyseal bone defects has been a major challenge in limb salvage surgery. Staged reconstruction as first described by Masquelet is a common strategy to deal with this problem in limb salvage surgery. One consequence of this technique is a time period of prolonged limited weightbearing while the segmental defect heals. The purpose of this study was to describe an adjunctive technique for stage II of the Masquelet procedure and retrospectively analyze the outcome and weight bearing progression of 3 patients who sustained femur fractures with significant bone loss and underwent this technique. A retrospective chart review was performed. The patients (2 males, 1 female with an average age of 36.6 years) all sustained segmental femur fractures which resulted in significant bone loss. Induced membrane technique with adjunct use of a fibular strut allograft was performed after initial stabilization and PMMA spacer placement. All three patients went on to union and full weight bearing after being treated by the described technique. All the patients were allowed toe-touch weight bearing immediately after surgery and all progressed to weight bearing as tolerated at an average of 3.6 months. Using a fibular strut allograft as an adjunct to the induced membrane technique serves as a biologic and mechanical scaffold and may allow earlier weightbearing.